Empirical assessment of e-learning on performance in principles of economics. (January 2015) - Aljamal, Ali; Cader, Hanas; Chiemeke, Charles; Speece, Mark
Abstract: This research assessed the effectiveness of online assignments in principles of macroeconomics classes. Students were divided into two groups where the first was required to submit online assignments (treatment) while the other was not (control). Standardized examinations were used as Pretest and Posttest to quantify the online assignments' impact on students' performance. Results showed no significant difference in performance between treatment and control groups. Furthermore, when looking closely at students' performance within the treatment group, results indicate that neither the use of online assignments, nor the degree or intensity of their use tends to have significant impact on students' performance.